Spiraling resources and emotional well-being: Longitudinal evidence for resource gain and loss spirals in COR and JD-R theories - Zeng, W.; Ma, S.; Wang, R.; Liao, H.; Cao, S.; Xu, Y.; Li, B. (Applied Psychology: An International Review, 2026)
Amid ongoing debate and limited empirical evidence regarding resource gain and loss spirals in conservation of resources (COR) and job demands–resources (JD-R) theories, this study examines how resource losses and gains shape emotional well-being trajectories over time, focusing on their momentum and magnitude. Drawing on experience sampling data from two longitudinal studies, we find compelling evidence for both gain and loss spirals with momentum and magnitude effects. Among the resource-providing factors (life-related and work-related support), work-related social support as job resources interacts with time to amplify their positive effects—individuals with higher social support experience a steeper upward trajectory of positive emotions and a faster decline in negative emotions. In contrast, among the resource-depleting job demands (workload and perceived work-related risks), workload interacts with time to intensify its detrimental impact, flattening the trajectory of positive emotions and suppressing emotional recovery. Furthermore, we identify a turning point in the U-shaped trajectory of positive emotions, indicating that resource loss and gain spirals are not strictly unidirectional but may reverse direction over time. These findings advance COR and JD-R theories by providing longitudinal evidence for resource gain and loss spirals and by integrating temporal dynamics into the understanding of how job resources and demands jointly shape emotional well-being over time.